The iodine molecule : insights into intra- and intermolecular perturbation in diatomic molecules /: insights into intra- and intermolecular perturbation in diatomic molecules. (2018) - Lukashov, Sergey; Petrov, Alexander; Pravilov, Anatoly
No abstract available